Generalized modality responses in primary sensory neurons of awake mice during the development of neuropathic pain - Sun, Linlin; Chen, Chao; Xiang, Xuwu; Guo, Shengyang; Yang, Guang (Frontiers in Neuroscience, 2024)
Introduction Peripheral sensory neurons serve as the initial responders to the external environment. How these neurons react to different sensory stimuli, such as mechanical or thermal forces applied to the skin, remains unclear. Methods Using in vivo two-photon Ca2+ imaging in the lumbar 4 dorsal root ganglion (DRG) of awake Thy1.2-GCaMP6s mice, we assessed neuronal responses to various mechanical (punctate or dynamic) and thermal forces (heat or cold) sequentially applied to the paw plantar surface. Results Our data indicate that in normal awake male mice, approximately 14 and 38% of DRG neurons respond to either single or multiple modalities of stimulation. Anesthesia substantially reduces the number of responsive neurons but does not alter the ratio of cells exhibiting single-modal responses versus multi-modal responses. Following peripheral nerve injury, DRG cells exhibit a more than 5.1-fold increase in spontaneous neuronal activity and a 1.5-fold increase in sensory stimulus-evoked activity. As neuropathic pain resulting from nerve injury progresses, the polymodal nature of sensory neurons intensifies. The polymodal population increases from 39.1 to 56.9%, while the modality-specific population decreases from 14.7 to 5.0% within a period of 5 days. Discussion Our study underscores polymodality as a significant characteristic of primary sensory neurons, which becomes more pronounced during the development of neuropathic pain.